ORGANIZATIONAL CULTURE DYNAMICS DURING CRISIS: KEY ENABLERS AND BARRIERS IN HOSPITAL CONTEXT - Meika Kurnia Puji Rahayu (ASIAN PUBLISHER, 2026)
This qualitative study aims to ascertain employees' comprehension of the new organizational culture and the facilitating and obstructive variables in its implementation within a hospital in Indonesia. The research background indicates that there was a need to shift the foundational principles and assumptions guiding organizational operations from innovation and competition to safety and resilience as a result of the catastrophe that transpired. This study examines two research questions: (1) To what extent do employees understand the company culture? (2) What are the facilitating and obstructive variables in the changing of organizational culture? The research design employs qualitative phenomenology using a case study approach. The data gathering methods employed in this study included (1) semi-structured interviews, (2) unstructured observations, and (3) documentation. Data analysis encompasses data reduction, data presentation, and data verification (formulating conclusions). The study's results reveal that certain staff remain uninformed about the new organizational culture within the institution. In addition, a contributing aspect to the implementation of organizational culture is the crisis (pandemic) itself. Elevated anxiety, augmented workload, inadequate communication, and absence of norms hinder the establishment of organizational culture. This study's findings suggest two recommendations, (1) there is a necessity for enhanced socialization of the new organizational culture, encompassing all work units, (2) the hospital must develop instruments, such standard operating procedures, posters, and organizational culture manuals, to aid in the internalization and execution of the new organizational culture.